Análise do efeito de tratamento térmico na resistência à corrosão da liga Mg-10Gd-1Eu-1Zn-0,2Zr visando aplicações biomédicas - Falci, Lucca Donatão Gonçalves (Universidade Federal de São Carlos, 2025)
Magnesium alloys containing rare-earth elements have emerged in recent years as promising alternatives to conventional Mg alloys, particularly due to their improved corrosion resistance. Initial studies on their application as bioabsorbable implants are already reported in the literature. The aim of this undergraduate thesis was to investigate the effect of a heat treatment protocol (solutionizing + aging) on the microstructure and corrosion resistance of the Mg-10Gd-1Eu-1Zn-0.2Zr (wt.%) alloy. Microstructural characterization techniques were combined with electrochemical methods for corrosion evaluation. Corrosion tests were conducted in simulated body fluid at 37 °C to replicate a bioactive environment. In both conditions (as-cast and heat-treated), a dendritic microstructure was observed, consisting of an α-Mg matrix and interdendritic secondary phases (W phase – (Mg,Zn)₃RE and 14H-LPSO phase). In the heat-treated alloy, the precipitation of a cubic Gd-rich phase was also identified. Comparison between the two conditions revealed coarsening of the microstructure, with the secondary dendritic arm spacing increasing from 44 to 97 µm and the fraction of interdendritic phases decreasing from 26% to 8%. Regarding corrosion behavior, heat treatment enhanced corrosion resistance, reducing the corrosion rate from 8.4 mm/year to 3.1 mm/year. Electrochemical tests indicated that the first 60 hours of immersion were critical for this improvement, suggesting the formation of a more stable protective film in the heat-treated alloy, which delayed the onset of degradation. The corrosion mechanism was similar in both conditions, differing mainly in intensity: an initial stage of protective film formation was followed by film breakdown and reformation of a porous, defective layer with reduced adherence to the metal.
Analysis of the effect of heat treatment on the corrosion resistance of the Mg-10Gd-1Eu-1Zn-0.2Zr alloy for biomedical applications
Keywords: Ligas de Mg; Terras raras; Tratamentos térmicos; Corrosão; Aplicações biomédicas; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA